The factors influence the tax assessment (quit rent) arrears in Kemaman / Syarifah Khatijah Syed Mohamed - Syed Mohamed, Syarifah Khatijah (2010)
Tax assessment or Quit Rent is not strange anymore amongst Malaysians. The study is done at Kemaman Municipal Council (Majlis Perbandaran Kemaman) by using secondary data which is value of tax assessment arrears reported from that institution. The period of study is from 2001 until 2010. The purpose of the study is to observe the factor that has potential to influence tax assessment arrears, which are average income, number of housing subject to tax and value of public utility provided by council. Findings of the study show that only two independent variables have significant influences which are average income and number of house. The research methodology use for this study is by using the secondary data from the institution and also economic data from the economic report. Meanwhile, in analyzing the data the Statistical Procedure of Social System (SPSS) is being used in order to transfer the data into output. As a conclusion from the study, most of the factor variables which are average income and number of housing subject to tax have an impact on the value of tax assessment arrears